Tvorba višjih harmonikov svetlobe - Hrast, Mateja (Matrika, 2014)
This article presents the process of generating coherent pulses of extreme ultra-violet light by interaction of a strong infra-red laser light with a gas. The mechanism of high harmonic generation is explained through a three step model, which classically describes the motion of an electron in the electromagnetic field of the laser. The article also describes the HHG installment at the University of Nova Gorica, which is going to be used for observing fast processes in matter.
Keywords: high harmonic generation; kvantna optika; laserji; lasers; quantum optics; tvorba višjih harmonikov